The Corona Virus Pandemic and Global Transformations: Making or Breaking International Orders? - G. Simons (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2020)
In the period of the 21st century leading up to the Corona Virus pandemic, there was increasing consensus that the global order that had existed since the end of the Cold War and the collapse of the Soviet Union where the unipolar hegemony of the United States was in relative decline, weakening and transforming. It was transforming from a unipolar to multipolar order, of course, the US was not going to leave the transformation uncontested in order to retain its privileged global position. The Corona Virus outbreak was a black swan event, it is also being used by various international actors to leverage opportunities caused by the weaknesses exposed in this extraordinary time. The US has been acting in an aggressive manner during the pandemic in an effort to try and weaken opponents and coerce friends in order to ‘cancel’ the pre-Corona Virus global transformations and retain its global hegemony.